(untitled) (MATEMATIKA, 2013)
The effect of an axial magnetic field, which varies inversely as the radius vector, on the velocity and temperature distribution in a swirling jet of a viscous incompressible electrically conducting fluid are studied. It is noted that the radial as well as tangential velocity decreases near the slit of the jet with the increase in the value of the magnetic interaction parameter. It is also observed that the effect of magnetic field is to increase the temperature for metal fluids whereas the reverse phenomenon happens for other fluids. These decelerated fluid particles move in the positive axial direction and the points where they exactly balance the motion of the incoming fluid have been calculated for different values of the magnetic interaction parameter. Keywords: Swirling jet; boundary layer; volume flux; transverse magnetic field. 2010 Mathematics Subject Classification: 76D25;76W05